Implementasi Energi Biogas Sebagai Energi Alternatif Pembangkit Listrik di Kabupaten Boyolali - Bagiyo Condro Purnomo,; Andi Widiyanto,; Suroto Munahar,; Anisa Hakim Purwantini,; Lintang Muliawanti,; Moch. Imron Rosyidi, (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this community service activity is to implement biogas energy as an alternative energy for micro-scale power plants, given the considerable potential possessed by Gedangan Village, Cepogo District, Boyolali Regency. The implementation method used in this activity is participatory rural appraisal approach that involves the active role of the community, to resolve problems or obstacles faced by dairy farmers with. The activity begins with the identification of the problems faced by the partners, then the design and implementation of the conversion of biogas to electricity as a micro-scale biogas power plant and ends with assistance to dairy farmers and the community. The result of the activity is production of biogas energy power plants in three locations with potential energy of 15 KW, which can be used to reduce management and maintenance costs for dairy cows and household needs as well. This activity also facilitates knowledge transfer to the people of Gedangan Village, Cepogo District, Boyolali Regency to be able to independently develop this biogas energy source. Thus this service activity provides considerable benefits for the residents of Gedangan Village, Cepogo District, Boyolali Regency in fulfilling energy from the conversion of biogas to electrical energy.